Double-arc harmonic gear profile design and meshing analysis for multi-section conjugation. (May 2019) - Chen, Guangsheng; Li, Huanhuan; Liu, Yang
Harmonic gear with double-circular-arc tooth profile has great advantage in the meshing performance. However, only the single cross section meshing or the adjustment of the flexible gear structure is considered to design the conjugate profile in the current research, which leads to the increase of the machining difficulty and is not consistent with the actual working condition of the harmonic gear transmission. Considering the cone deformation of the flexible gear shell, in the direction perpendicular to the axis, the conjugate of the flexible gear teeth is different from that of the rigid gear. Therefore, based on the envelope theory, a double circular arc tooth profile of rigid gear can be designed to achieve multi-section conjugation. Then MATLAB programming is used to simulate the flexible teeth in multi-section. At the same time, according to the assembly simulation, it is shown that the different parts of the flexible gear are engaged with the rigid gear continuously in the meshing process. The results show that on the premise of not adjusting the structure of the gear, this method is more consistent with the actual working condition of the harmonic gear compared with the method of only designing the tooth profile of the middle section conjugate. During the meshing process, there is a double conjugate phenomenon in some regions. By means of parameter adjustment, effective conjugation can be realized in a wider range. When the wave generator cam rotates 67.13°, the tooth profile of the middle section is separated from the rigid gear, and the pairs of meshing teeth are increased and the load capacity is strong. Through the finite element analysis, the dynamic characteristics of the harmonic gear device under normal working conditions are studied, and it is proved that the design parameters of the device can fully meet the strength requirements. A prototype of the double circular arc harmonic gear reducer is manufactured. And by means of assembly and dynamic performance test, the accuracy error of return is 105.2 s. The continuous conjugate meshing with multiple sections can improve the stability and bearing capacity of the transmission and is suitable for actual production and processing. The continuous conjugate meshing with multiple sections can improve the stability and bearing capacity of the transmission, and this is suitable for actual production and processing of rigid gear.